Functional safety-oriented hazard analysis and risk assessment for vehicular fuel cell systems - Ke Song; Ruili Jia; Pengyu Huang; Xing Huang; Boqiang Zhang; Feiqiang Li (Heliyon)
Functional safety is an emerging trend for safety design in the automobile industry. This study is an innovative exploration of a hazard analysis and quantitative risk assessment (QRA) methodology based on the functional safety of vehicular fuel cell systems. In this study, the potential hazards that fuel cell vehicles may encounter during operation were identified using the automobile generic hazard list. The failure modes and influences of the main components of the fuel cell system were determined via hazard and operability studies. Furthermore, the risks and consequences of the fuel cell system were explored using the QRA method. The failure frequency and unavailability of the fuel-cell system were calculated, and the architecture was optimized using a redundant design with a focus on hydrogen safety. The results showed that the optimized system architecture could effectively reduce the hazard of hydrogen leakage, and the unavailability and failure frequency of hydrogen leakage risk were reduced by 94.4 % and 36.8 %, respectively. Thus, this study provides powerful insights for future research and improvement of vehicular fuel cell systems.